The Effect of the Administration of Bovine Xenograft on the Accelerated Healing of Femoral Fracture in Domestic Dogs - Pratama, Anggi Muhtar; Abadi, Rais Dwi; Ratrisono, Raka Bayu; Budhi, Setyo; Kristanto, Dwi (Veterinary Biomedical and Clinical Journal, 2023)
Bovine xenografting is a method of grafting bovine bones to other species. This study aimed to determine the effect of the administration of bovine xenografts on accelerated healing in domestic dogs with femoral fractures. This study used a total of 4 dogs (two individuals as the treatment group and other two as the control group) diagnosed with diaphyseal femoral fractures. The bovine xenograft in the form of hydroxyapatite (Ca10(PO4)6(OH)) was synthesized in this study. The femur fracture surgery was carried out using the open reduction and internal fixation (ORIF) method, followed by the administration of 10 grams of Hydroxyapatite powder from the bovine bone in the fracture area, in the treatment group. The control group was not treated with Hydroxyapatite. Radiographic examinations were carried out on days 0, 14, and 45 post-operation. The parameters observed included the formation of radiopaque mass on the radiographic imaging, indicating the formation of calli around the fracture area. The radiographic examination showed that in the treatment group, the radiopaque mass was apparent on day 14 post-operation while it was not observable in the control group. On day 45 post-operation, the mass was more clearly visible in the treatment group, while it was barely visible in the control group. This research indicated that bovine xenograft has the potential to accelerate the fracture healing process in domestic dogs